CRIME OF MONEY LAUNDERING REFLECTED IN THE RECENT MANDATORY JURISPRUDENCE OF THE HIGH COURT OF CASSATION AND JUSTICE - Constantin NEDELCU (Challenges of the Knowledge Society)
This study represents an in-depth analysis of the rulings of the High Court of Cassation and Justice, by the Panel for clarifying certain legal issues. In actuality, it is about the way in which the Supreme Court ruled when issuing such a decision, respectively the Decision no. 16/2016, the conclusions reached being explained and sometimes criticized. In addition, the study identifies other aspects that receive different classification solutions in the judicial practice, which generates a non-unitary practice in criminal matters.